ANALISIS KEBUTUHAN GURU TERHADAP PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA BERBASIS ANDROID - Sandy Yudha; Nurfajriani Nurfajriani; Ramlan Silaban (PROSIDING SEMINAR KIMIA, 2022)
This study aims to describe the teacher's need for android-based chemistry learning media that can support the chemistry learning process in the classroom. The needs analysis is carried out based on the first stage of the ADDIE model, namely (analyst) or analysis. The method used in this research is a survey method. The participants of this study were 10 chemistry teachers from schools in Binjai City and Langkat Regency. Data was collected using a questionnaire with qualitative data types. The questionnaire was distributed using a google form so that respondents could fill out the questionnaire online. The results of the study were analyzed descriptively and obtained data that the media that teachers often use such as projectors, PPT/LCD with a percentage of 80%, while android-based chemistry learning media are still very rarely used. The obstacle is the manufacture, use and development of media which is quite difficult so that teachers feel less interested in making media and lack of ideas on what media is good for chemistry learning. So they suggest that tutorials are given in the creation and use of learning media. Keywords: needs analysis, learning media, chemistry